Could Lipid Profile be Used as a Marker of Autonomous Cortisol Secretion in Patients with Adrenal Incidentalomas? - Mintziori, Gesthimani; Georgiou, Thomas; Anagnostis, Panagiotis; Adamidou, Fotini; Efstathiadou, Zoe; Panagiotou, Athanasios; Kita, Marina (Hormone and Metabolic Research, 2018)
Adrenal incidentalomas (AIs) have been associated with an increased risk of metabolic syndrome and dyslipidemia, though evidence regarding the latter is limited. Lipid abnormalities in patients with AIs have been associated with subclinical hypercortisolism. The current study aims to test whether lipid profile in patients with AIs predicts “autonomous cortisol secretion” (ACS). Patients with AIs found on either computerized tomography (CT) or magnetic resonance imaging (MRI), were included in a prospective cohort study. All patients were followed up for at least three years. Alterations in their hormonal and lipid profiles were recorded. Ninety-four patients (69 women) harboring 111 AIs were included. There were no differences between patients with ACS and those without, with respect to their baseline lipid profile [total cholesterol, low-density-lipoprotein cholesterol (LDL-C), triglycerides, high-density lipoprotein cholesterol (HDL-C) and non-HDL-C] and blood pressure (systolic and diastolic). Non-HDL-C concentrations decreased over time (Repeated Measures ANOVA, p=0.013), despite patients’ body mass index (BMI) remaining unchanged. Logistic regression analysis revealed that the only predictor of ACS was the size of AIs, as calculated by CT or MRI. The current study demonstrated that lipid profile at baseline or during follow-up cannot predict ACS in patients with AIs. However, larger AIs may have a greater probability of ACS.
Keywords: adrenal incidentalomas; autonomous cortisol secretion; subclinical Cushing; dyslipidemia